2014
DOI: 10.1037/h0099852
|View full text |Cite
|
Sign up to set email alerts
|

Moral injury, suicidal ideation, and suicide attempts in a military sample.

Abstract: Moral injury entails emotional distress associated with perceived violations of one's moral code and has been proposed to be a possible contributor to self-injurious thoughts and behaviors (SITB) among military personnel. Three dimensions of moral injury have previously been empirically derived: transgressions committed by others (Transgressions-Others), transgressions committed by oneself (Transgressions-Self), and perceived betrayal by others (Betrayal). The current study examined the relationship of these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
188
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(211 citation statements)
references
References 31 publications
21
188
2
Order By: Relevance
“…Furthermore, guilt was significantly associated with suicide ideation in both samples, which aligns with previous research (A. O. Bryan, Bryan, et al, 2014;C. J. Bryan, Ray-Sannerud, et al, 2013;Hendin & Haas, 1991).…”
Section: Table 1 Means Standard Deviations and Intercorrelations Osupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, guilt was significantly associated with suicide ideation in both samples, which aligns with previous research (A. O. Bryan, Bryan, et al, 2014;C. J. Bryan, Ray-Sannerud, et al, 2013;Hendin & Haas, 1991).…”
Section: Table 1 Means Standard Deviations and Intercorrelations Osupporting
confidence: 90%
“…Recent research has supported an association among moral injury, suicide ideation, and suicide attempts, and has also suggested that moral injury (especially distress about one's own moral transgressions) may serve as a mechanism that underlies the relationship of posttraumatic stress with suiciderelated outcomes (A. O. Bryan, Bryan, et al, 2014). Research also suggests that self-forgiveness following perceived inappropriate actions is associated with decreased risk for suicide attempts and moderates the effect of posttraumatic stress on risk for suicide attempts among military personnel and veterans (A. O. Bryan, Theriault, .…”
Section: Table 1 Means Standard Deviations and Intercorrelations Omentioning
confidence: 97%
“…Moral injury is a syndrome characterized by emotional responses of guilt and shame following perceived violation of moral values. Moral injury has been related to myriad social and functional difficulties, including SI (Bryan et al, 2014). Research is needed to better understand the relationship between trauma-related guilt and moral injury.…”
Section: Discussionmentioning
confidence: 99%
“…Negative self-concept, in particular, appears to be especially key to understanding the emergence of suicidal thoughts and behaviors within the context of PTSD. Guilt, remorse, self-blame, and self-criticism not only increase risk of suicidal thoughts and behaviors [20][21][22][23][24]; accumulating evidence suggests they explain the relationship of PTSD with suicide-related outcomes [22,25,26]. Guilt has also been found to be a risk factor for the later development of other trauma-related sequelae such as depression and substance use disorders [27][28][29][30][31], each of which serves as a suicide risk factor in its own right.…”
Section: Conceptualizing Suicidal Behaviormentioning
confidence: 99%